Misunderstanding and Sensemaking among Juvenile Probation Officers Working with Evidence-Based Practices - Ingel, Sydney N. (Victims & offenders, 2022)
Evidence-based practices and programs (EBPs) have been adopted in juvenile probation agencies nationwide to maximize the number of successful probation cases. However, various pragmatic studies have found that JPOs are not yielding the expected benefits when compared to efficacy studies. Using focus group and survey data, the current study sought to increase our understanding of the gap between pragmatic and efficacy studies in juvenile probation settings by examining JPOs’ perceptions and utilization of EBPs. The findings suggest that JPOs are misunderstanding how to use EBPs in daily practice, leaving them with negative perceptions of EBPs. Implications for improving JPO understanding and use of EBPs are discussed.